Reading philosophy of language : selected texts with interactive commentary - Hornsby, Jennifer; Longworth, Guy (Blackwell Pub., 2006)
Designed for readers new to the subject, "Reading Philosophy of Language" presents key texts in the philosophy of language together with helpful editorial guidance. The book features seminal texts by leading figures in the field, such as Austin, Chomsky, Davidson, Dummett and Searle; presents three texts on each of five key topics: speech and performance; meaning and truth; knowledge of language; meaning and compositionality; and, non-literal meaning. A volume introduction from the editors outlines the subject's principal concerns. Introductions to each chapter locate the pieces in context and explain relevant terminology and theories. Interactive commentaries help readers to engage with the texts.